2019
DOI: 10.3390/nano9060823
|View full text |Cite
|
Sign up to set email alerts
|

“Three-Bullets” Loaded Mesoporous Silica Nanoparticles for Combined Photo/Chemotherapy

Abstract: This contribution reports the design, preparation, photophysical and photochemical characterization, as well as a preliminary biological evaluation of mesoporous silica nanoparticles (MSNs) covalently integrating a nitric oxide (NO) photodonor (NOPD) and a singlet oxygen (1O2) photosensitizer (PS) and encapsulating the anticancer doxorubicin (DOX) in a noncovalent fashion. These MSNs bind the NOPD mainly in their inner part and the PS in their outer part in order to judiciously exploit the different diffusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 47 publications
(55 reference statements)
0
9
0
Order By: Relevance
“…Recent research has shown that exogenous NO has a therapeutic effect on human diseases at appropriate concentrations. For example, NO can synergistically enhance the anticancer ability of some anticancer medicines [35,36,37]. Additionally, it has been identified that exogenous NO can actively inhibit bacteria proliferation or directly eliminate bacteria in a relatively high concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has shown that exogenous NO has a therapeutic effect on human diseases at appropriate concentrations. For example, NO can synergistically enhance the anticancer ability of some anticancer medicines [35,36,37]. Additionally, it has been identified that exogenous NO can actively inhibit bacteria proliferation or directly eliminate bacteria in a relatively high concentration.…”
Section: Introductionmentioning
confidence: 99%
“…22,48,74 The surface functionalization enables the delivery of therapeutics, such as NO or traditional chemotherapeutics, and also promotes a targeted delivery to cancerous cells. 74,75 Among different nanoparticles, AuNPs have been one…”
Section: Cytotoxicity Of No-releasing Polymer-functionalized Nanoparticles Against Tumoral and Non-tumoral Cell Linesmentioning
confidence: 99%
“…While more ordered pore system enhanced the diffusion of water through the cavities, resulting in faster NO-release kinetics, more heterogenous pore structures hindered the solvent diffusion and resulted in more sustained NO-release profiles. In another work, 66 the amine groups in the outer surface of a NH2functionalized mesoporous silica were used to covalently attach erythrosine, a singlet oxygen photosensitizer (PS), while the internal surfaces were used to conjugate a nitro anilinederivative as a photoactive NO-donor. The antitumoral drug doxorubicin (Dox) was further encapsulated into the porous matrix, generating a multidrug carrier.…”
Section: Chemical Attachment Of Gas Donorsmentioning
confidence: 99%